2015
DOI: 10.3354/esr00699
|View full text |Cite
|
Sign up to set email alerts
|

Expert elicitation of seasonal abundance of North Atlantic right whales Eubalaena glacialis in the mid-Atlantic

Abstract: North Atlantic right whales Eubalaena glacialis are among the most endangered of the large whales. Although protected since 1935, their abundance has remained low. Right whales occupy the Atlantic Ocean from southern Greenland and the Gulf of St. Lawrence south to Florida. The highly industrialized mid-Atlantic region is part of the right whales' migratory corridor, and gaps in knowledge of their movements through this region have limited the ability to make informed decisions about management of the species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In this study, concurrent acoustic monitoring by the Cornell University Lab of Ornithology revealed a longer period of occurrence than the shorter seasonal period that was detected by aerial surveys . Re cent studies of E. glacialis distribution in coastal areas that used a combination of acoustic and visual assessment techniques found that aerial surveys were useful for estimating abundance and identifying individuals, but that acoustic monitoring detected occurrence over longer periods of time (Whitt et al 2013, Hodge et al 2015, Oedekoven et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, concurrent acoustic monitoring by the Cornell University Lab of Ornithology revealed a longer period of occurrence than the shorter seasonal period that was detected by aerial surveys . Re cent studies of E. glacialis distribution in coastal areas that used a combination of acoustic and visual assessment techniques found that aerial surveys were useful for estimating abundance and identifying individuals, but that acoustic monitoring detected occurrence over longer periods of time (Whitt et al 2013, Hodge et al 2015, Oedekoven et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…This has been referred to as an interim PCoD approach (King et al, 2015) because this function should be replaced with one based on empirically derived values as soon as they become available. In some of these cases, structured elicitation of information from multiple experts (known as expert elicitation) can provide both estimates of the appropriate parameters and a measure of the associated uncertainty (King et al, 2015;Martin et al, 2012;Oedekoven, Fleishman, Hamilton, Clark, & Schick, 2015). In alternative, the measured effect of changes in prey availability can be used as a proxy for the relation between energy intake and vital rates (Williams, Thomas, Ashe, Clark, & Hammond, 2016).…”
Section: A D Irec T Link B E T Ween E Xp Osure and Vital R Ate Smentioning
confidence: 99%
“…Related to the small sample size, sample selection bias could also impact the results. Overestimation has been observed when gathering data from both small‐scale fishers (O'Donnell, Pajaro, & Vincent, ) and scientific experts (Burgman et al, ; Oedekoven, Fleishman, Hamilton, Clark, & Schick, ). While the four‐step elicitation method we employed is more likely to reduce overconfidence than three‐point procedures (Speirs‐Bridge et al, ), it is possible that an overconfident attitude towards risk influenced several of our fishers’ judgments (Figure ).…”
Section: Discussionmentioning
confidence: 99%